Experimental Evaluation of Tali Bamboo Trusses with FRP Connections for Sustainable Structural Applications - Budiono; Arif Mudianto (Advance Sustainable Science Engineering and Technology, 2025)
Tali Bamboo is a local material that is widely utilized in traditional construction due to its availability, strength, and flexibility. However, weaknesses in the connection system are a major obstacle in its application as a structural element. This research aims to evaluate the strength and stiffness of tali bamboo joints using Fiber Reinforced Polymer (FRP) as joint reinforcement in plane trusses. The method used was experimental testing of three truss models with varying numbers of FRP laminate layers (1, 2, and 3 layers) combined with Polyvinyl Acetate (PVAc) adhesive and epoxy resin. Tests were conducted with center point loading to assess the performance of the connection. The results showed that the connection with 2 layers of FRP was able to withstand the maximum load optimally, or was able to withstand an average maximum load of 25.2 kN with an average deflection of 3.1 cm. The highest value reached 30 kN and a deflection of 4.0 cm, indicating optimal efficiency and strength. The physical properties of tali bamboo in the internode section are weaker than those in the book section, but still generally meet the criteria for structural materials. The implications of this study suggest that the use of double-layered FRP connections in tali bamboo can be an effective solution in improving the performance of plane truss structures, although further testing is required for more complex connections between truss elements.